DAMPAK STRATEGI KOPING MASYARAKAT JAWA DI MASA PANDEMI COVID-19 - Faruq, Faruq; Syahrina, Hanum Midya; Sabani, Nureyzwan; Rahmawati, Siti; Sukmakarti, Laksmy Dewi; Prihartanti, Nanik (UI Scholars Hub, 2022)
The Coping Strategy is a way that is considered effective in overcoming the problems experienced by the Indonesian people during the COVID-19 pandemic, especially the Javanese people. The implementation of the coping strategy will have a positive impact on the lives of the Javanese people in carrying out daily activities. The research method used in this study is qualitative to uncover the meaning of social problems experienced by individuals or communities, with the focus of research being the impact of implementing the coping strategy of the Javanese community during the COVID-19 pandemic. The data collection technique used in this study was an open questionnaire disseminated through the media of google forms. The subjects of this study were 100 respondents of Javanese people with adult categories domiciled in the Surakarta residency area (Surakarta City, Karanganyar Regency, Sragen Regency, Wonogiri Regency, Sukoharjo Regency, Klaten Regency, and Boyolali Regency) for at least two years. The field data that have been obtained are analyzed using thematic analysis. The result of this study is the positive impact felt by the Javanese people after implementing coping strategies during the pandemic, namely changes in each individual and feeling positive feelings. The results of this study provide information to the public that the implementation of coping strategies has a positive impact on carrying out daily activities.